CALL AND CALENDAR. (Computer (00189162), 2006)
The article presents a calendar of events concerning the computer industry. A conference titled "VL/HCC 2006, IEEE Symp. on Visual Languages & Human-Centric Computing" is scheduled on September 4-8, 2006 in Brighton, England. The "ASAP 2006, 17th IEEE Int'l Conf. on Application-Specific Systems, Architecture & Processors" is slated on September 11-13, 2006 in Steamboat Springs, Colorado.